2022
DOI: 10.1002/aic.17761
|View full text |Cite
|
Sign up to set email alerts
|

AI models for correlation of physical properties in system of 1DMA2P‐CO2‐H2O

Abstract: In this work, the density, viscosity, and specific heat capacity of pure 1-dimethylamino-2-propanol (1DMA2P) as well as aqueous unloaded and CO 2 -loaded 1DMA2P solution (with a CO 2 loading of 0.04-0.70 mol CO 2 /mol amine) were measured over the 1DMA2P concentration range of 0.5-3.0 mol/L and temperature range of 293-323 K.The observed experimental results of these thermophysical properties of the 1DMA2P-H 2 O-CO 2 system were correlated using empirical models as well as artificial neural network (ANN) model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(9 citation statements)
references
References 36 publications
(55 reference statements)
0
9
0
Order By: Relevance
“…Carbon dioxide (CO 2 ) has been accused as one of major responsible contributors for the increasingly serious climate problem due to the rising concentration of CO 2 in the atmosphere . CO 2 capture technology has been investigated widely for controlling CO 2 emissions from industrial flue gas, and the amine-based chemical absorption process has been regarded as the most mature method for the post-combustion CO 2 capture. , However, the large-scale application of amine-based CO 2 capture technology is still challenging, mainly because of the huge heat requirement in the amine solvent regeneration process (CO 2 desorption). , Many efforts have been made to overcome the drawbacks of the amine-based CO 2 capture technology including the development of new absorbents and the use of other new technologies for enhancing the CO 2 capture efficiency. It was reported that the heat cost for solvent regeneration contributes more than 70% of the total heat cost, which constrains the industrial application of this technology. , …”
Section: Introductionmentioning
confidence: 99%
“…Carbon dioxide (CO 2 ) has been accused as one of major responsible contributors for the increasingly serious climate problem due to the rising concentration of CO 2 in the atmosphere . CO 2 capture technology has been investigated widely for controlling CO 2 emissions from industrial flue gas, and the amine-based chemical absorption process has been regarded as the most mature method for the post-combustion CO 2 capture. , However, the large-scale application of amine-based CO 2 capture technology is still challenging, mainly because of the huge heat requirement in the amine solvent regeneration process (CO 2 desorption). , Many efforts have been made to overcome the drawbacks of the amine-based CO 2 capture technology including the development of new absorbents and the use of other new technologies for enhancing the CO 2 capture efficiency. It was reported that the heat cost for solvent regeneration contributes more than 70% of the total heat cost, which constrains the industrial application of this technology. , …”
Section: Introductionmentioning
confidence: 99%
“…Useful solution properties and the value of mass transfer coefficients for stirred cell were reported too. These outcomes will assist in the development of artificial neural network (ANN) models, such as those developed by Liu et al for the properties of the tertiary amine 1DMA2P, and generic artificial intelligence (AI) models similar to those of Quan et al for predicting mass transfer coefficients in the absorbers. Finally, low-temperature desorption of AHPD/PZ mixtures over the γ-Al 2 O 3 catalyst was also explored to check for possible reduction in the stripping energy constraint.…”
Section: Introductionmentioning
confidence: 99%
“…ML models have the ability to learn complex nonlinear data patterns, and they can be effectively used for the estimation or prediction of state variables using easily available descriptor data . Although ML models have gained a lot of attention in recent years in the fields of finance, telecommunications, language processing, etc., the studies reporting the ML models for the prediction of CO 2 solubility in different solvents are very few. Further, ML models have been employed for carbon capture, utilization and storage, discovery of porous materials for carbon capture, prediction of CO 2 absorption, prediction of thermodynamic properties of CO 2 in the solvent, study of the correlations between physical properties (density, viscosity, and specific heat capacity) and CO 2 loading, prediction of mass transfer coefficients in the CO 2 absorber, design of new solvents, , etc. Furthermore, there are a few studies reporting ML models for the prediction of CO 2 solubility in different, physical, chemical, and ionic solvents, and the corresponding summary points are presented in Table , including the details on the type of CO 2 solvent, the ML model developed, input data used for model building, etc.…”
Section: Introductionmentioning
confidence: 99%